Why Are Wives Vulnerable? An Analysis of Domestic Violence in Manado - Lambonan, Marthin Luther; Gerungan, Mario A.; Sepang, Rony (Jurnal Ilmu Hukum Kyadiren, 2026)
Domestic violence against wives constitutes a violation of human rights that continues to occur frequently, despite its regulation under Law Number 23 of 2004 on the Elimination of Domestic Violence. This study aims to analyze the prevalence of physical violence against wives in Manado City and to identify the dominant factors influencing it. The research employs an empirical juridical method with a descriptive-analytical approach, utilizing questionnaires and interviews. The findings indicate that the prevalence of physical violence is 4.44% within the general population and is absent among highly educated women. The dominant factors include low levels of education, economic dependence, unequal power relations, and patriarchal cultural norms. It is concluded that physical violence within the household is a complex phenomenon; therefore, a comprehensive strategy is required, encompassing women’s empowerment and the strengthening of legal protection mechanisms.